Decoration of the internal structure of mesoporous chromium terephthalate MIL-101 with NiO using atomic layer deposition. - Jeong, Myung-Geun; Kim, Dae Han; Lee, Su-Kyung; Lee, Ju Ha; Han, Sang Wook; Park, Eun Ji; Cychosz, Katie A.; Thommes, Matthias; Hwang, Young Kyu; Chang, Jong-San; Kim, Young Dok (Microporous and Mesoporous Materials, 2016)
Mesoporous chromium terephthalate MIL-101 was modified with NiO via at. layer deposition (ALD) process using bis(cyclopentadienyl)nickel (Ni(Cp)2) as a metal precursor and O2 as an oxidizing agent, resp. Based on the results of transmission electron microscopy (TEM), N2 and Ar isotherms, XPS, and inductively coupled plasma-at. emission spectroscopy (ICP-AES), we show that the deposited NiO nanoparticles were distributed inside internal mesoporous cages as well as on the external surface of MIL-101(Cr). Studies using in situ XPS show that NiO selectively occupied ligand sites without affecting metal sites of MIL-101. The NiO deposition using ALD enhanced thermal stability of MIL-101 compared to that without NiO and provided catalytic activity for CO oxidn., i.e., ALD provided novel chem. functionality to the metal-org. frameworks (MOFs). [on SciFinder(R)]
Keywords: decoration internal structure mesoporous chromium terephthalate MIL 101; nickel oxide atomic layer deposition